1991
DOI: 10.1007/bf00008534
|View full text |Cite
|
Sign up to set email alerts
|

Caddis larvae cases (Trichoptera, Limnephilidae) as anti-predatory devices against brown trout and sculpin

Abstract: Brown trout (Salmo trutta L.) and sculpin (Cottus gobio L.) predation on the cased limnephilid larvae Glyphotaelius pellucidus (Retz.) (weak, broad leaf case), Limnephilus pantodapus McLachl. (weak, long cylindrical leaf case), L. rhombicus (L.) (rigid, 'hedgehog' case) and Potamophylax cingulatus (Steph.) (rigid, cylindrical mineral case) was studied in the laboratory. The proportion of larvae ingested was significantly higher in brown trout than in sculpin for all four prey species. Brown trout captured larv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Selective feeding by large, generalist herbivores, including waterfowl (Sondergaard et al 1996, Van Donk and Otte 1996, Weisner et al 1997, Santamaria 2002, crayfish (Lodge and Lorman 1987, Lodge 1991, Lodge et al 1994, Dorn and Wojdak 2004, mammals (Qvarnemark and Sheldon 2004), and fish (Van Donk and Otte 1996), can alter the abundance and species composition of freshwater plant communities and drive plant assemblages towards dominance by chemically defended plants (Parker et al 2006). Although macroinvertebrates are often abundant on submersed aquatic plants (Brusven et al 1990, Bowden 1999, Hutchens et al 2004, and suffer intense predation from omnivorous crayfish (Lodge et al 1994), fish (Sheldon 1987, Johansson 1991, Flecker and Townsend 1994, and waterfowl (Marklund et al 2002), the feeding and host-plant preferences of small, plant-associated grazers relative to the feeding preferences of larger consumers in the same freshwater system have rarely been considered.…”
mentioning
confidence: 99%
“…Selective feeding by large, generalist herbivores, including waterfowl (Sondergaard et al 1996, Van Donk and Otte 1996, Weisner et al 1997, Santamaria 2002, crayfish (Lodge and Lorman 1987, Lodge 1991, Lodge et al 1994, Dorn and Wojdak 2004, mammals (Qvarnemark and Sheldon 2004), and fish (Van Donk and Otte 1996), can alter the abundance and species composition of freshwater plant communities and drive plant assemblages towards dominance by chemically defended plants (Parker et al 2006). Although macroinvertebrates are often abundant on submersed aquatic plants (Brusven et al 1990, Bowden 1999, Hutchens et al 2004, and suffer intense predation from omnivorous crayfish (Lodge et al 1994), fish (Sheldon 1987, Johansson 1991, Flecker and Townsend 1994, and waterfowl (Marklund et al 2002), the feeding and host-plant preferences of small, plant-associated grazers relative to the feeding preferences of larger consumers in the same freshwater system have rarely been considered.…”
mentioning
confidence: 99%
“…This dissimilar pattern is consistent with the different hunting techniques of those predators. Dragonfly naiads and brown trout rely on physically damaging the case (puncturing, rupturing or crushing) for successful predation (personal observation), and mineral cases offer greater protection than organic ones against them (Otto and Svensson 1980;Johansson 1991; Nislow and Molles 1993;Johansson and Englund 1995). In contrast, fire salamander larvae need to separate the larvae from its case to consume it (see above), as shown for ambystomatid salamanders (Holomuzki 1983;Wissinger et al 1999), and both organic and mineral cases seem to be of the same anti-predator value against them.…”
Section: Case Selection Behaviourmentioning
confidence: 98%
“…Previous studies have shown that the mineral cases of the genus Potamophylax and other limnephilids are of greater defensive value than organic ones against brown trout and dragonflies that rely on crushing or puncturing the case for successful predation (Otto and Svensson 1980;Johansson 1991;Otto and Johansson 1995;Nislow and Molles 1993). Gut content analyses have revealed that brown trout eat larvae of Potamophylax and other limnephilids with their cases (Rincón 1993).…”
Section: Natural Historymentioning
confidence: 99%
See 1 more Smart Citation
“…The degree to which Notonecta larvae opt for safety instead of better food is dependent upon agespecific vulnerability (Sih 1981). It has been suggested that odonate larvae have evolved 2 main life-styles in response to vertebrate predators: a "slow" life-style with low activity in the presence of vertebrate predators and a "fast" life-style with high activity and rapid energetic rates in the absence of predators (Johansson 1991). A higher level of activity may be related to a lower reaction time (Johansson & Johansson 1992).…”
Section: )mentioning
confidence: 99%